Enhancing the temporal response of modified porous silicon-based CO gas sensor. (August 2021) - Alwan, Alwan M.; Abed, Husam R.; Rashid, Rasha Bashar
Highlights: Synthesize of macro porous silicon by laser-assisted etching process. Coating gold nanoparticles by ion reduction method by dipping the porous silicon samples in HAuCl4 solution. Increase the thermal conductivity of the porous silicon by incorporating Au nanoparticles. The decay time of the gas sensor device is reduced by 50% for that Au modified porous silicon. High sensitivity was obtained towards CO gas molecules with lower concentration. Abstract: In this paper, the role of gold nanoparticles on the temporal response of a porous silicon gas sensor has been studied. The porous layer was prepared by a laser-assisted etching process using 810 nm wavelength and 2 W infrared laser diode as an illumination photonics source. The experimental etching conditions involve 20 mA/cm 2 current density and 10 min etching time. Gold nanoparticles were incorporated into porous silicon structures via the ion reduction process. The characteristics of sensors were studied comprehensively by SEM, XRD, and the electrical properties were investigated for the sensor before and after the gold nanoparticles incorporation process. The obtained results manifested that the decay time of the sensor was reduced by a factor almost greater than (50%) as compared with the bare porous silicon sensor. The results were discussed based on the role of gold nanoparticles that enhanced the thermal conductivity of porous silicon. A higher thermal conductivity of about (130 W/mK) due to the gold nanoparticles was achieved as compared with the bare porous silicon gas sensor.